2021
DOI: 10.1200/go.21.00253
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cancer Care in Northern Tanzania: Patient and Health-System Predictors for Delayed Presentation

Abstract: PURPOSE Cancer is a growing problem in Africa, and delays in receiving timely cancer care often results in poorer outcomes. The purpose of this study was to identify the patient and health-system factors associated with delayed cancer care in adults living in the Northern Zone of Tanzania. PATIENTS AND METHODS Between July 2018 and July 2019, we surveyed adult patients presenting to an oncology clinic in Northern Tanzania. Delayed presentation was defined as 12 weeks or longer from initial symptoms to presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…The fact that patients from rural areas are more likely (odds ratio 1.46) to use HM than those from urban areas indicates the importance of availability and geographical accessibility of treatment in specialized centers. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that patients from rural areas are more likely (odds ratio 1.46) to use HM than those from urban areas indicates the importance of availability and geographical accessibility of treatment in specialized centers. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The fact that patients from rural areas are more likely (odds ratio 1.46) to use HM than those from urban areas indicates the importance of availability and geographical accessibility of treatment in specialized centers. 10 By far, the highest share in the survey has been the socially expected answers of sociocultural factors of own belief, recommendation, and tradition. Use of HM appears as the common way of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Multiple factors influence the timely diagnosis of cancer in Africa such as cultural beliefs, educational level, transportation, and poverty. [17][18][19] However, unlike higher resource settings, wait time for initiation of treatment is long in Ethiopia, and during this period, a substantial proportion of patients are lost to follow-up and presumably died without receiving treatment. Long wait time are associated with worse outcomes in head and neck cancers; a study from Taiwan showed worse outcomes after a 40-day delay, and a larger Dutch study showed poorer outcomes after a 90-day delay.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons are manifold including limited financial resources both on patients and service provider side, poor knowledge about cancer also on the provider side resulting in misdiagnosis, and a generally low health literacy rate among the general population facilitating misbeliefs and trust in alternative and less effective medical practices [ 3 ].…”
mentioning
confidence: 99%